Diagnóstico de la situación sociolaboral de las personas con discapacidad en el cantón Esmeraldas, durante los años 2011-2012. - Angulo Guerrero, Marcia (2014)
This work is supported in field research, documentary and literature under the quantitative approach - qualitative, since the purpose was to determine the social and employment situation of people with disabilities in the canton Esmeraldas during 2011-2012. It was based on the major bibliographical sources at national and international level allowing to know the different definitions in regard to disability.